The 2022 Campaign on the Palaeolithic of the Zarqa Valley - Parenti, Fabio; Scardia, Giancarlo [UNESP]; Cerqueira, João Carlos [UNESP]; Belarmino, Simone; Faure, Martine; Sen, Sevket (The University of Jordan, 2024)
New surveys in August-September 2022 in the upper Zarqa Valley have increased the number of stratified archaeological sites from Early and Middle Pleistocene colluvial/alluvial units. The main results are: 1) the extension of the archaeological-bearing Dawqara Formation (Early Pleistocene) to the northern margin of the Zarqa Governorate, with the recovery of new artefacts, 2) the discovery of rodent teeth remains in an archaeological outcrop of Dawqara Formation 3) the discovery of three new stratified middle Acheulean sites, with minimal disturbance and favourable conditions for future excavations. Within the Dawqara and Birayn Formations the occurrence of several palaeosols indicates recurrent pedogenic phases in the Zarqa Valley and provided new material for palaeoenvironmental characterization of the archaeological sites. Conservation requirements and threats to the sites are also discussed with regard to the whole archaeological heritage of the oldest prehistory of Levant.
Keywords: Jordan; Lower Palaeolithic; Pleistocene; Stratigraphy; Taphonomy; Zarqa Valley